Narrowing Perceptual Sensitivity to the Native Language in Infancy: Exogenous Influences on Developmental Timing - Mayada Elsabbagh; Annette Hohenberger; Ruth Campos; Jo Van Herwegen; Josette Serres; Scania de Schonen; Gisa Aschersleben; Annette Karmiloff-Smith (Behavioral Sciences, 2013)
The infancy literature situates the perceptual narrowing of speech sounds at around 10 months of age, but little is known about the mechanisms that influence individual differences in this developmental milestone. We hypothesized that such differences might in part be explained by characteristics of mother-child interaction. Infant sensitivity to syllables from their native tongue was compared longitudinally to sensitivity to non-native phonemes, at 6 months and again at 10 months. We replicated previous findings that at the group level, both 6- and 10- month-olds were able to discriminate contrasts in their native language, but only 6-month-olds succeeded in discriminating contrasts in the non-native language. However, when discrimination was assessed for separate groups on the basis of mother-child interaction—a ‘high contingency group’ and a ‘moderate contingency’ group—the vast majority of infants in both groups showed the expected developmental pattern by 10 months, but only infants in the ‘high contingency’ group showed early specialization for their native phonemes by failing to discriminate non-native contrasts at 6-months. The findings suggest that the quality of mother-child interaction is one of the exogenous factors influencing the timing of infant specialization for speech processing.